2019
DOI: 10.1088/2053-1591/ab6000
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and application of acrylate-based poly ionic liquid for corrosion protection of C1020 steel In hydrochloric acid solution

Abstract: Poly ionic liquids (PIL) are eco-friendly in addition to being sustainable compounds that can be easily prepared and tailored according to the application. In this study, a novel PIL polymer based on acrylate was chemically synthesised via free radical polymerization method controlled by quenching the reversible reaction. The prepared 1-Butyl-3 Methylimidazolium Acrylate polymer (PAL) was characterised using FTIR as well as NMR to confirm the chemical structure. GPC was employed to determine the average molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The cathodic reaction is predominantly slowed in the system without the inhibitor. 32 , 33 The corrosion inhibitor compounds can be labeled as the anodic or cathodic type when the shift in E corr is at higher than 85 mV with respect to the blank solution. 34 E corr differs by less than 85 mV between the inhibited and uninhibited systems, implying that the GS is a mixed-type inhibitor.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cathodic reaction is predominantly slowed in the system without the inhibitor. 32 , 33 The corrosion inhibitor compounds can be labeled as the anodic or cathodic type when the shift in E corr is at higher than 85 mV with respect to the blank solution. 34 E corr differs by less than 85 mV between the inhibited and uninhibited systems, implying that the GS is a mixed-type inhibitor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…When compared to those of the system without the inhibitor, the potential curves move toward higher negative potentials, showing that the cathodic reaction is largely slowed. The cathodic reaction is predominantly slowed in the system without the inhibitor. , The corrosion inhibitor compounds can be labeled as the anodic or cathodic type when the shift in E corr is at higher than 85 mV with respect to the blank solution …”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure 6 shows the FTIR spectra for polyamide inert support layer and PIL augmented membranes to monitor the changes in functionalities on PIL augmentation. The polyimide base membrane and both PIL modified membranes exhibit two distinctive peaks around 1535 cm −1 to 1642cm −1 which correspond to the amide moieties from polyimide support and was seen in case of virgin membrane as well as PIL modified membranes [ 36 ]. Kamaz et al reported the pressure-assisted deposition PILs from 2 vinyl and 4 vinyl pyridines on same polyamide support.…”
Section: Resultsmentioning
confidence: 99%
“…Further research and implementation of polyionic liquids as novel antibacterial agents can decrease antibiotic drug resistance [ 33 , 34 ]. Grafting PIL brushes on the membrane surface was reported to exhibit the electrical response in presence of external oscillating electric field [ 35 , 36 ]. A pressure-assisted self-assembly method was used to deposit the selective poly(ionic) liquid layer onto the polyimide support [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potentiodynamic polarization curves were obtained in the potential range of −250 to +250 mV with respect to open-circuit potential (OCP) at a scan rate of 0.5 mV s −1 . The inhibition efficiency (IE) was calculated using the following relation: 31 where: is the corrosion current density of blank sample and I corr is the corrosion current density of inhibited sample.…”
Section: Methodsmentioning
confidence: 99%